Emerging trends in the agri-food sector: digitalisation and shift to plant-based diets - Hassoun, Abdo; Boukid, Fatma; Pasqualone, Antonella; Bryant, Christopher J.; Garcia-Garcia, Guillermo; Carlos, Parra-López; Jagtap, Sandeep; Trollman, Hana; Cropotova, Janna; Barba, Francisco J. (Elsevier, 2022)
Our planet is currently facing unprecedented interconnected environmental, societal, and economic dilemmas due to climate change, the outbreak of pandemics and wars, among others. These global challenges pose direct threats to food security and safety and clearly show the urgent need for innovative scientific solutions and technological approaches. Backed by the current alarming situation, many food-related trends have emerged in recent years in response to these global issues. This review looks at two megatrends in agriculture and the food industry; the shift to vegetable diets and the digital transformation in food production and consumption patterns. On one side, several innovative technologies and protein sources have been associated with more sustainable food systems and enhanced nutritional quality and safety. On the other side, many digital advanced technologies (e.g., artificial intelligence, big data, the Internet of Things, blockchain, and 3D printing) have been increasingly applied in smart farms and smart food factories to improve food system outcomes. Increasing adoption of vegetal innovations and harnessing Industry 4.0 technologies along the food supply chain have the potential to enable efficient digital and ecological transitions.
Keywords: Digitalisation; Food industry 4.0; Precision agriculture; Smart food factory; Sustainability; Vegan; Vegetarian diets